How to reply to referees’ comments when submitting manuscripts for publication - Williams, Hywel C. (Elsevier, 2004)
Background: The publication of articles in peer-reviewed scientific journals is a fairly complex and stepwise process that involves responding to referees’ comments. Little guidance is available in the biomedical literature on how to deal with such comments. Objective: The objective of this article is to provide guidance to novice writers on dealing with peer review comments in a way that maximizes the chance of subsequent acceptance. Methods: This will be a literature review and review of the author’s experience as a writer and referee. Results: Where possible, the author should consider revising and resubmitting rather than sending an article elsewhere. A structured layout for responding to referees’ comments is suggested that includes the 3 golden rules: (1) respond completely; (2) respond politely; and (3) respond with evidence. Conclusion: Responding to referees’ comments requires the writer to overcome any feelings of personal attack, and to instead concentrate on addressing referees’ concerns in a courteous, objective, and evidencebased way. (J Am Acad Dermatol 2004;51:79-83.)